2020
DOI: 10.3390/ma13061453
|View full text |Cite
|
Sign up to set email alerts
|

The New Technologies Developed from Laser Shock Processing

Abstract: Laser shock processing (LSP) is an advanced material surface hardening technology that can significantly improve mechanical properties and extend service life by using the stress effect generated by laser-induced plasma shock waves, which has been increasingly applied in the processing fields of metallic materials and alloys. With the rapidly development of modern industry, many new technologies developed from LSP have emerged, which broadens the application of LSP and enriches its technical theory. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…LSP techniques have wide application in aerospace, nuclear, biomedical, marine, and automotive industries. In the aerospace industry, LSP is used in passenger and military flights to enhance the fatigue performance of the compressor blade, landing gears, shafts, valves, discs, and complex forming of wing surfaces [ 159 , 160 ]. Hammersley et al [ 159 ] demonstrated the effect of LSP on fatigue strength of turbine fan blades, which are made of Ti6Al4V.…”
Section: Applications and Future Directionsmentioning
confidence: 99%
“…LSP techniques have wide application in aerospace, nuclear, biomedical, marine, and automotive industries. In the aerospace industry, LSP is used in passenger and military flights to enhance the fatigue performance of the compressor blade, landing gears, shafts, valves, discs, and complex forming of wing surfaces [ 159 , 160 ]. Hammersley et al [ 159 ] demonstrated the effect of LSP on fatigue strength of turbine fan blades, which are made of Ti6Al4V.…”
Section: Applications and Future Directionsmentioning
confidence: 99%
“…Problems of the observation the laser-induced optical breakdown and shock processes in matter as Nonlinear Optical (NLO) and Relaxed Optical (RO) processes are connected with acoustic (thermal) and electromagnetic (plasma and Nonlinear optical) nature [2] [7] [8] [9] [28]- [33]. These processes may be connected with diffractive stratification of laser beam, self-focusing, self-trapping, generation of supercontinuum radiation (ordered: Cherenkov radiation, and disorder: plasma radiation) [7] [8] [34] [35] [36].…”
Section: Laser-induced Optical Breakdownmentioning
confidence: 99%
“…These processes may be connected with diffractive stratification of laser beam, self-focusing, self-trapping, generation of supercontinuum radiation (ordered: Cherenkov radiation, and disorder: plasma radiation) [7] [8] [34] [35] [36]. We present this problem from one point of view for all media from gases to solid [2] [3] [7] [8] [28]- [33]. Unfortunately, the first attempt of observation this problem in main detail in whole are represented in [7] [8] only.…”
Section: Laser-induced Optical Breakdownmentioning
confidence: 99%
See 2 more Smart Citations